Analysis of Blimp-1 and PD-1/PD-L1 Immune Checkpoint in an Autoimmune Thyroiditis Animal Model - Xue Zhang; Xiaoshu Lv; Mengya Chen; Haixia Liu (International Journal of Endocrinology)
Objective. B lymphocyte-induced maturation protein 1 (Blimp-1) and programmed cell death protein 1 (PD-1) have opposing roles in the development of T cells; however, the mechanism of autoimmune thyroiditis- (AIT-) associated abortion is unclear. The present study investigated the expression of Blimp-1 and PD-1/PD-ligand 1 (PD-L1) in AIT-associated pregnancy loss and elucidated the related signaling pathway involving in the inflammatory response. Methods. An experimental fetal loss model with autoimmune thyroiditis was established after murine thyroglobulin- (mTg-) immunized CBA/J female mice mating with Balb/c males. ELISA was employed to investigate the TgAb level in the serum of CBA/J female mice. The expression of Blimp-1, PD-1/PD-L1, mammalian target protein rapamycin (mTOR), and Foxp3 proteins in the placenta and spleen was detected through immunofluorescence staining and western blotting. Results. ELISA indicated that the serum TgAb level in the mTg group was higher than that in the control group (P<0.001). Fetal resorption rates increased in the mTg group compared with those in the control group (45.63% vs. 3.1%, P<0.05). Blimp-1 levels in the placenta and spleen were higher in the AIT-related miscarriage group than in the control group. However, the expression of PD-1/PD-L1 and Foxp3 was significantly decreased in the placenta and spleen in the AIT-related miscarriage group. Conclusion. Blimp-1 participates in the pathogenesis of autoimmune thyroid disease-associated pregnancy loss through the inflammatory immune response, which is potentially mediated through the PD-1/PD-L1 signaling pathway.